2014
DOI: 10.1002/chem.201404208
|View full text |Cite
|
Sign up to set email alerts
|

ATRP/OMRP/CCT Interplay in Styrene Polymerization Mediated by Iron(II) Complexes: A DFT Study of the α‐Diimine System

Abstract: A DFT study of various model systems has addressed the interference of catalytic chain transfer (CCT) as a function of the R(2) substituent in the atom-transfer radical polymerization (ATRP) of styrene catalyzed by [FeCl2 (R(1) N=C(R(2))C(R(2))=NR(1))] complexes. All model systems used R(1) =CH3 in place of the experimental Cy and tBu substituents and 1-phenylethyl in place of the polystyrene (PS) chain. A mechanistic investigation of 1) ATRP activation, 2) radical trapping in organometallic-mediated radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
(143 reference statements)
3
16
0
Order By: Relevance
“…This behavior suggests that CCT is the predominant termination mechanism, rather than bimolecular termination. This mechanism has been previously observed for both β-ketiminate 8 and α-diimine 29,30…”
Section: Resultssupporting
confidence: 76%
“…This behavior suggests that CCT is the predominant termination mechanism, rather than bimolecular termination. This mechanism has been previously observed for both β-ketiminate 8 and α-diimine 29,30…”
Section: Resultssupporting
confidence: 76%
“…6b, 8b and 7b (left to right) compared (32,47) These findings were found to accord with those of Johansson and Swart, who also recently published a computational study of this Fe-α-diimine system (48). Johansson and Swart also argued that the electron-withdrawing/donating parasubstituents of the 2,3-diarylated α-diimine complexes act to modulate the relative energies of the ATRP and CCT pathways by charge-transfer effects.…”
Section: Figure 5 Experimentally-and Computationally-derived Spin Stsupporting
confidence: 85%
“…Poli and co-workers recently reported a computational investigation of the mechanism of CRP mediated by this family of Fe II -α-diimines (47). In contrast to a previous report (32), they found that the ligands themselves do not control the spin-state of the various complexes.…”
Section: Understanding Interplay With Computational Chemistrymentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, a computational study has indicated that the preferred pathway to CCT, starting from the Fe III OMRP dormant species, is homolytic bond breaking followed by direct hydrogen‐atom transfer (Scheme , path a), which occurs essentially without any overbarrier 25. For both α‐diimine and diaminobis(phenolato) systems ( 6 and 7 ), the Fe II complex (Mt x /L) has a four‐coordinate distorted tetrahedral structure and a high‐spin state ( S =2), whereas the CCT intermediate (HMt x +1 /L) and the OMRP dormant species (P n Mt x +1 /L) have an S =3/2 ground state.…”
Section: Mechanistic Interplays Of Omrpmentioning
confidence: 99%